2021
DOI: 10.1177/20563051211048413
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Over Vaccination: Ideological Differences in Twitter Expression About COVID-19 Vaccine Favorability and Specific Hesitancy Concerns

Abstract: Vaccine hesitancy has been a growing public health issue, but during COVID-19, understanding vaccine hesitancy and promote vaccine favorability takes on a troubling immediacy. With the growing political polarization on scientific issues, the COVID-19 vaccine-related sentiment has recently been divided across ideological lines. This study aims to understand how vaccine favorability and specific vaccine-related concerns including possible side effects, distrust in medical professionals, and conspiratorial belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…The COVID‐19 pandemic, declared in March 2020 (World Health Organization, 2020), presented significant challenges for individuals (e.g., Social Metrics Commission, 2020; Wu et al, 2021), intergroup relations (e.g., Jiang et al, 2021; Prosser et al, 2020), and societies (e.g. Abrams et al, 2021; Carothers & Press, 2020; Mazey & Richardson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID‐19 pandemic, declared in March 2020 (World Health Organization, 2020), presented significant challenges for individuals (e.g., Social Metrics Commission, 2020; Wu et al, 2021), intergroup relations (e.g., Jiang et al, 2021; Prosser et al, 2020), and societies (e.g. Abrams et al, 2021; Carothers & Press, 2020; Mazey & Richardson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of the pandemic, whilst the medical burden is slowly diminishing, the other, presumably longlasting effects, come to the forefront. The polarizing effect that the debate around vaccination brought or intensified in various societies is one such noteworthy effect, with politicization of the debate along ideological lines (Jiang et al, 2021); another is the impact that the increasing level of disinformation has on public trust in institutions and in geopolitical allies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, according to their "natural immunity theory", barricades to microbes, like physical distancing and masks, deteriorate our immune system, and vaccines are just one more artificial loaded weapon that has targeted our immune system [19]. Nonetheless, while the emergent political polarization on scientific matters has caused the COVID-19 vaccine-related feeling to be separated across sociopolitical lines [20], COVID-19 continues to contaminate and kill; so, extensive immunization becomes indispensable for combating the virus [21]. Alternatively, using inoculation to battle the COVID-19 illness will not work effectively unless the majority of the people get immunized [22], whose hesitancy may derive from specific concerns about side effects, distrust of medical professions, conspiratorial beliefs [23][24][25], low levels of trust in political institutions, a low degree of education, and a feeling of alienation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, inquiry has exhibited that those who are more conformist are less likely to have confidence in medical professionals [32,33], and are more expected to confirm conspiracy schemes such as vaccine threats are being censored by pharmaceutical corporations [34]. Also, analysis has shown that while liberal people seem to emphasize vaccine development and its role in termination of contagion, conservative persons discuss the probable wrongdoing in vaccine studies and related broadcasts [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation